Video Based Learning Sebagai Tren Media Pembelajaran Di Era 4.0 - Hesty Maulida Eka Putry; Venia Nuzulul 'Adila; Rofiatus Sholeha; Danial Hilmi (Tarbiyatuna: Jurnal Pendidikan Ilmiah, 2020)
This paper is a literature review related to video based learning as a learning media trend in the 4.0 era. Issues that will be discussed in this paper include; industrial revolution, educational revolution, media trends in the 4.0 era, to video based learning. Data collection methods by collecting library data, reading and recording, and processing literacy materials related to these issues. Because the media is one system that plays an important role in the development of learners to increase innovative and effective knowledge. This discussion emphasizes video media as a learning tool that can help students in rationally illustrating material Arabic learning is difficult learning for students, with the existence of video media that is trending in the 4.0 era this will help students in the learning process, learning Arabic using media video makes students easy to understand the content of the lesson with clear illustrations without making students to illustrate abstractly, then the presence of video media as a means of learning Arabic will make it easier for students to understand the content of the material provided by the teacher.